The effect of FOXA2 rs1209523 on glucose-related phenotypes and risk of type 2 diabetes in Danish individuals - Banasik, Karina (BioMed Central, 2012)
BACKGROUND: Variations within the FOXA family have been studied for a putative contribution to the risk of type 2 diabetes (T2D), and recently the minor T-allele of FOXA2 rs1209523 was reported to associate with decreased fasting plasma glucose levels in a study using a weighted false discovery rate control procedure to enhance the statistical power of genome wide association studies in detecting associations between low-frequency variants and a given trait. Thus, the primary aim of this study was to investigate whether the minor T-allele of rs1205923 in FOXA2 associated with 1) decreased fasting plasma glucose and 2) a lower risk of developing T2D. Secondly, we investigated whether rs1205923 in FOXA2 associated with other glucose-related phenotypes. METHODS: The variant was genotyped in Danish individuals from four different study populations using KASPar(® )PCR SNP genotyping system. We examined for associations of the FOXA2 genotype with fasting plasma glucose and estimates of insulin release and insulin sensitivity following an oral glucose tolerance test in 6,162 Danish individuals from the population-based Inter99 study while association with T2D risk was assessed in 10,196 Danish individuals including four different study populations. RESULTS: The FOXA2 rs1209523 was not associated with fasting plasma glucose (effect size (β) = -0.03 mmol/l (95%CI: -0.07; 0.01), p = 0.2) in glucose-tolerant individuals from the general Danish population. Furthermore, when employing a case-control setting the variant showed no association with T2D (odds ratio (OR) = 0.82 (95%CI: 0.62-1.07), p = 0.1) among Danish individuals. However, when we performed the analysis in a subset of 6,022 non-obese individuals (BMI < 30 kg/m(2)) an association with T2D was observed (OR = 0.68 (95%CI: 0.49-0.94), p = 0.02). Also, several indices of insulin release and β-cell function were associated with the minor T-allele of FOXA2 rs1209523 in non-obese individuals. CONCLUSIONS: We failed to replicate association of the minor T-allele of FOXA2 rs1209523 with fasting plasma glucose in a population based sample of glucose tolerant individuals. More extensive studies are needed in order to fully elucidate the potential role of FOXA2 in glucose homeostasis.